A high-resolution melting approach for the simultaneous differentiation of five human babesiosis–causing Babesia species - Yanbo Wang; Shangdi Zhang; Xiaoyun Li; Yueli Nian; Xinyue Liu; Junlong Liu; Hong Yin; Guiquan Guan; Jinming Wang (Parasites & Vectors, 2023)
Abstract Background Six species of apicomplexan parasites of the genus Babesia, namely B. microti, B. divergens, B. duncani, B. motasi, B. crassa–like and B. venatorum, are considered to be the primary causal agents of human babesiosis in endemic areas. These six species possess variable degrees of virulence for their primary hosts. Therefore, the accurate identification of these species is critical for the adoption of appropriate therapeutic strategies. Methods We developed a real-time PCR–high-resolution melting (qPCR-HRM) approach targeting 18S ribosomal RNA gene of five Babesia spp. based on melting temperature (T m) and genotype confidence percentage values. This approach was then evaluated using 429 blood samples collected from patients with a history of tick bites, 120 DNA samples mixed with plasmids and 80 laboratory-infected animal samples. Results The sensitivity and specificity of the proposed qPCR-HRM method were 95% and 100%, respectively, and the detection limit was 1–100 copies of the plasmid with the cloned target gene. The detection level depended on the species of Babesia analyzed. The primers designed in this study ensured not only the high interspecific specificity of our proposed method but also a high versatility for different isolates from the same species worldwide. Additionally, the Tm obtained from the prepared plasmid standard is theoretically suitable for identifying isolates of all known sequences of the five Babesia species. Conclusions The developed detection method provides a useful tool for the epidemiological investigation of human babesiosis and pre-transfusion screening. Graphical Abstract